Single-Phase Voltage Source Multi-Level Inverter Hysteresis SVPWM Reconfigurable Fault-Tolerant Control Method - Guohua Li; Liangjun Wang; Feng Li (Energies, 2022)
A hysteresis space vector pulse width modulation (SVPWM) reconfigurable fault-tolerant method for single-phase voltage source multi-level inverter with current tracking is proposed. Firstly, the influence of single switch open circuit fault and double switches open circuit fault on the voltage vector of the inverter is analyzed, and on this basis, the equivalent replacement of the voltage vector is obtained by using the topology reconstruction of the inverter, and the redundant voltage vectors with overlapping positions are preferred for equivalent replacement. If there are no coincident non-fault vectors, the other non-fault vectors with the closest position and effect are selected. The fault-tolerant method does not need the switching operation between the main power switching device and spare power switching device of the inverter, and can directly control the on–off process of the inverter reconfiguration unit through the driving signal of insulated gate bipolar translator (IGBT), which is simple and stable. Under the conditions of single switch open circuit and most double switches open circuit, the output current of the inverter can accurately track the reference current.